2021
DOI: 10.12659/msm.929949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine on Perioperative Hemodynamics and Myocardial Protection in Thoracoscopic-Assisted Thoracic Surgery

Abstract: Background This study aimed to clarify the protective role of dexmedetomidine in thoracoscopic-assisted thoracic surgery (TATS), including control of the intraoperative heart rate, blood pressure, and myocardial injury markers. Material/Methods The patients who underwent TATS were divided into 2 equal groups: the dexmedetomidine group (dexmedetomidine pumped at 0.5 μg/kg for >10 min before the administration of anesthesia and at 0.5 μg/kg in the maintenance period) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…In the current study, dp/dt in each dexmedetomidine group was significantly lower than the basic values after dexmedetomidine loading dose use, indicating that loading doses of 1 or 0.5 μg/kg could both inhibit myocardial contractility. While the dp/dt in group D 3 was significantly higher than those in groups D 1 and D 2 at 1 h in PACU and had no significant difference compared with that in group C, illustrating that lower dose of dexmedetomidine at 0.5 μg/kg/h significantly improve the cardiac prognosis, which was consistent with the previous studies [ 36 38 ]. Hence, lower dose dexmedetomidine in D 3 had no significant adverse effects on myocardial function during perioperative period.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, dp/dt in each dexmedetomidine group was significantly lower than the basic values after dexmedetomidine loading dose use, indicating that loading doses of 1 or 0.5 μg/kg could both inhibit myocardial contractility. While the dp/dt in group D 3 was significantly higher than those in groups D 1 and D 2 at 1 h in PACU and had no significant difference compared with that in group C, illustrating that lower dose of dexmedetomidine at 0.5 μg/kg/h significantly improve the cardiac prognosis, which was consistent with the previous studies [ 36 38 ]. Hence, lower dose dexmedetomidine in D 3 had no significant adverse effects on myocardial function during perioperative period.…”
Section: Discussionsupporting
confidence: 89%
“…Before anesthesia, patients often have decreased blood volume due to adverse emotions to surgical treatment, causing excessive changes in blood pressure and heart rate as well as reduced body tolerance. [23] suggested that Dex injection before anesthesia could effectively relieve perioperative hemodynamics and protect myocardial cells in thoracic surgery. Elgebaly et al (2020) [24] found that Dex was more effective before anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Hemodynamic stability ensures tissue perfusion of vital organs, such as the heart and brain. Moreover, a slight decrease in heart rate reduces myocardial oxygen consumption, which may protect the myocardium [ [33] , [34] , [35] ]. Nevertheless, heart rate monitoring needs to be emphasized.…”
Section: Discussionmentioning
confidence: 99%